An Empirical Analysis of the Financing Policies Adopted by Brazilian Public Companies - Pedro Góes Monteiro de Oliveira; Fernando Nascimento Oliveira (Revista Brasileira de Finanças, 2009)
The Static Tradeoff and Pecking Order models speciﬁed in Shyam-Sunder and Myers (1999) were employed to analyze the ﬁnancing policies adopted by Brazilian public ﬁrms. At a ﬁrst glance, it seems that both models correctly describe the way in which ﬁrms in the sample ﬁnance their investments, although the Pecking Order model explains a greater percentage of the time series variance in the debt level. But when the power to reject the alternative hypothesis of each of the two models is considered, we conclude that the adopted policy is actually of the pecking order type. The factors that inﬂuence the decision to issue debt or equity to ﬁnance cash deﬁcits, for the ﬁrms in the sample, were also studied with the help of two nonlinear probability models of the “Probit” type. The results show that equity is issued when market conditions are favorable, and not only when there is a substantial risk of default, pointing to a pecking order policy of the “complex” type.